2019
DOI: 10.1080/21691401.2019.1602049
|View full text |Cite
|
Sign up to set email alerts
|

A novel cross-linked haemoglobin-based oxygen carrier is beneficial to sepsis in rats

Abstract: Pathological hypoxia-induced organ dysfunction contributes to the high mortality of sepsis. Because of the microcirculation dysfunction following severe sepsis, it is difficult for erythrocytes to transport oxygen to hypoxic tissues. Haemoglobin-based oxygen carriers (HBOCs) are capable of delivering oxygen to hypoxic tissues. The aim of this study is to observe the potential benefits of a novel bovinederived, non-polymerized, cell-free HBOC solution, YQ23, on sepsis in rats. Cecum ligation and puncture was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…Previous studies found that HBOC improved oxygen delivery and consumption of the body by carrying oxygen. Our previous studies found that HBOC could improve oxygen delivery and consumption in rats with haemorrhagic shock and sepsis [11,19]; Li et al's [16] study found that HBOC could very much improve the survival rate of haemorrhagic shock as well as the PaO 2 of the body. The present study showed that HBOC could improve mitochondrial function after haemorrhagic shock.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies found that HBOC improved oxygen delivery and consumption of the body by carrying oxygen. Our previous studies found that HBOC could improve oxygen delivery and consumption in rats with haemorrhagic shock and sepsis [11,19]; Li et al's [16] study found that HBOC could very much improve the survival rate of haemorrhagic shock as well as the PaO 2 of the body. The present study showed that HBOC could improve mitochondrial function after haemorrhagic shock.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to improving the survival rate, HBOC also has protective effects on organ function in various diseases. A study by Li and Kuang found that HBOC had excellent protective effects on the liver, kidney, brain and other important organs in rats with haemorrhagic shock and sepsis [11,19]; Li et al's study found that HBOC had (HA, green, A), heparan sulphate (HS, green, B) and chondroitin sulphate (CS, green, C) levels in VECs (bar ¼ 25 lm) (n ¼ 8 observations per group). Data are presented as mean ± SD, each group contains eight observations, Ã p < 0.05 and ÃÃ p < 0.01 as compared with normal group, #p < 0.05 and ##p < 0.01 as compared with hypoxia group, @p < 0.05 and @@p < 0.01 as compared with LR group.…”
Section: Discussionmentioning
confidence: 98%
“…To better understand differences in the efficacy between T‐state and R‐state PolybHb, further studies in animals under pathological conditions are necessary, since high or low O 2 affinity might be beneficial depending on the type of pathological model used. Other HBOCs have been tested and show that HBOCs improve recovery from septic shock, hemorrhagic shock, and myocardial infarction 34–38 . The high viscosity of these materials may preclude their use in certain scenarios where the PolybHb comprises most of the blood (such as after significant hemorrhage), as patients may not tolerate the increased cardiac load, particularly when the heart is already compromised.…”
Section: Discussionmentioning
confidence: 99%
“…cardiac injury and cardiac insufficiency can be as high as 40-50% in patients with sepsis (1). in case of impaired cardiac function, the mortality rate can increase from 20 to 70%, and it continues to increase in a number of countries (2).…”
Section: Introductionmentioning
confidence: 99%
“…in case of impaired cardiac function, the mortality rate can increase from 20 to 70%, and it continues to increase in a number of countries (2). Studies have shown that early improvement of cardiac function can be achieved to significantly improve patient survival rates (1,2). The mechanism of cardiac insufficiency in sepsis is complex.…”
Section: Introductionmentioning
confidence: 99%